Opening the Cages of Faujasite-Type Zeolite. - Qin, Zhengxing; Cychosz, Katie A.; Melinte, Georgian; El Siblani, Hussein; Gilson, Jean-Pierre; Thommes, Matthias; Fernandez, Christian; Mintova, Svetlana; Ersen, Ovidiu; Valtchev, Valentin (Journal of the American Chemical Society, 2017)
Zeolites are widely used in industrial processes, mostly as catalysts or adsorbents. Increasing their micropore vol. could further improve their already exceptional catalytic and sepn. performances. We report a tunable extn. of zeolite framework cations (Si, Al) on a faujasite-type zeolite, the archetype of mol. sieves with cages and the most widely used as a catalyst and sorbent; this results in ca. 10% higher micropore vol. with limited impact on its thermal stability. This increased micropore vol. results from the opening of some of the small (sodalite) cages, otherwise inaccessible to most mols. As more active sites become accessible, the catalytic performances for these modified zeolites are substantially improved. The method, based on etching with NH4F, is also applicable to other cage-contg. microporous mol. sieves, where some of the most industrially relevant zeolites are found. [on SciFinder(R)]
Keywords: opening cage faujasite zeolite silicon aluminum micropore vol